(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
All of us know what importance does the Indian Evidence Act, 1872 hold under a trial, which also has a pre-occupied impact on the minds of lawyers or any other legal person. This Act gives a prominent existence to all the facts and pieces of evidence affiliated with the crime scene which is considered to be amongst the main components governed by the said Act. Coming to another crucial part of this Act, which is the “Opinion of Experts”. Evidence Act helps to bring in a frame the opinion of experts which may be pertinent for a case to rely on and also sticks some kind of evidentiary value to be favored from such opinions. Further opinions can be placidly divided into the experts’ like- Handwriting expert, Foreign Law, Science and Art and Electronic evidence. Such opinions are governed by the Indian Evidence Act, 1872 from Sections 45 to 51 (inclusive of Section 45-A and 47-A). In this article, the researcher will deal with all such aspects of the “Opinion of examiner of the Electronic evidence.” Who are these “Experts” and what is the value of Expert’s opinion?